The Impact of Reflective Writing on Empathy Development among Medical Students: A Systematic Review and Narrative Synthesis: Impact of Reflective Writing on Empathy Development Among Medical Students - Shomaila, .; Akram, Badar; Amin, Sarah; Shaukat, Sidrah; Saleem, Sadaf; Fatima, Sadia (Pakistan Journal of Health Sciences, 2025)
Empathy is central to patient-centered care but often declines during medical training. Reflective writing has emerged as a strategy to strengthen empathy by fostering emotional awareness, ethical reasoning, and self-reflection. Objectives: To evaluate the effectiveness of reflective writing in enhancing empathy among undergraduate medical students and identify features influencing its success. Methods: A systematic search of PubMed, ScienceDirect, ERIC, and Google Scholar (January 2020–July 2025) was conducted following PRISMA 2020 guidelines. Thirty-four records were identified, 4 duplicates removed, and 16 excluded during screening. Eighteen full texts were reviewed, and 15 studies met eligibility criteria. Eligible designs included qualitative, quantitative, and mixed-methods research; conceptual contributions with structured reflective models were also retained. Data on participants, interventions, reflective frameworks, and empathy measures were extracted. Risk of bias was assessed using adapted CASP and ROBINS-I criteria. Results: Of the 15 included studies, 3 demonstrated statistically significant empathy improvements using validated tools (p<0.0125, p=0.04). One study showed no significant change, while 9 reported descriptive or thematic improvements, such as enhanced ethical reasoning and emotional engagement. Two studies provided anecdotal evidence, and 2 were theoretical. Risk-of-bias assessment indicated most studies were of moderate quality, limited by small samples, self-reported outcomes, and absence of controls. Conclusion: Reflective writing is a promising, low-cost educational tool for nurturing empathy in medical students, especially when structured, facilitated, and supported by feedback. Future studies should employ validated instruments, larger sample sizes, and longitudinal follow-up to confirm sustained effects.